Complex Orofacial Reconstruction with the Intrinsic Chimeric Flap - Maldonado, Andrés A.; Silva, Amanda K.; Humphries, Laura S.; Gottlieb, Lawrence J. (Journal of Reconstructive Microsurgery, 2017)
Background Ablation of locally advanced or recurrent head and neck cancer often results in large composite orofacial defects with limited recipient vessels. These complex defects lend well to intrinsic chimeric flap reconstruction, which allows greater ability to inset various flap component tissue types than composite flaps and requires only one set of microvascular anastomoses.Methods A retrospective chart review was performed on all patients who underwent orofacial reconstruction with an intrinsic chimeric free flap from 2002 to 2015. Flaps with only one tissue type, such as two separate skin paddles with no additional component, were not considered chimeric flaps and therefore not included in this report. Patient demographic data, defect, and flap characteristics, as well as complications and outcomes were analyzed to create a guide for flap selection. Univariate and multivariate analysis was performed to determine risk factors for flap take-back and failure.Results Seventy-five patients underwent orofacial intrinsic chimeric free flap reconstruction. Results were organized based on defect characteristics to create a guide for flap selection. The number of chimeric flap components and operation duration were independently statistically associated with flap take-backs (p < 0.05). There were two (3%) total and five (7%) partial flap losses. Average follow-up time was 32.7 months.Conclusions Intrinsic chimeric flaps provide a versatile and elegant reconstructive option for a variety of complex orofacial defects. We provide a guide to facilitate decision making in flap selection for these challenging reconstructions and report factors associated with flap take-backs and losses.
Keywords: intrinsic chimeric flap; head and neck reconstruction; free flap design